2020
DOI: 10.1038/s41598-020-59617-9
|View full text |Cite|
|
Sign up to set email alerts
|

New insights into cheddar cheese microbiota-metabolome relationships revealed by integrative analysis of multi-omics data

Abstract: Cheese microbiota and metabolites and their inter-relationships that underpin specific cheese quality attributes remain poorly understood. Here we report that multi-omics and integrative data analysis (multiple co-inertia analysis, MciA) can be used to gain deeper insights into these relationships and identify microbiota and metabolite fingerprints that could be used to monitor product quality and authenticity. Our study into different brands of artisanal and industrial cheddar cheeses showed that Streptococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 44 publications
1
31
1
Order By: Relevance
“…has demonstrated that strong and significant associations exist between cheese microbiota and metabolites. To our knowledge, some of these associations have not been previously described, such as the positive association between the levels of phenylalanine and the presence of Thermus, while others were consistent with the known biochemical characteristics of bacterial species, such as the association between urease-positive S. thermophilus and decreased levels of urea (Afshari et al, 2020).…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…has demonstrated that strong and significant associations exist between cheese microbiota and metabolites. To our knowledge, some of these associations have not been previously described, such as the positive association between the levels of phenylalanine and the presence of Thermus, while others were consistent with the known biochemical characteristics of bacterial species, such as the association between urease-positive S. thermophilus and decreased levels of urea (Afshari et al, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…Total DNA was extracted from 200 mg of each cheese sample using a PowerSoil DNA Isolation Kit (MO BIO Laboratories, Inc., Carlsbad, CA, United States) following the manufacturer's instructions. DNA purity and concentration were determined and PCR amplification and DNA sequencing of bacterial 16S rRNA genes were performed as described previously (Afshari et al, 2020). Briefly, the V4 region of DNA was amplified using primers 515F and 806R.…”
Section: S Rrna-based Cheese Microbiota Analysismentioning
confidence: 99%
See 3 more Smart Citations